Percursos críticos e tradutórios da nação: Argentina e Brasil - Adriana Silvina Pagano (1996)
This work makes a comparative reading of translation and critical discourse from the perspective of nation-building in two Latin American countries: Argentina and Brazil. The period covered ranges from the political independence of those nations, in the early 19th century, to the 1960s. The analysis of Argentine and Brazilian translators' metalanguage shows certain recurrent representations of the nation, such as the desert and the disjunctive civilization-barbarism in Argentina and the ideas of recreation and fusion in Brazil. The presence of those representations within the critical discourse developed in those nations suggests that the interaction criticism-translation plays a significant part in the discourse of nation-building. This thesis points to the specificity of the discourse of nation-building in the countries studied as well as to the existence of shared areas between them. Analogous movements of translation of the classics and of the romantic writers throughout the development of a national discourse in the 19th century, together with the expansion oftranslation in the 1940s and 50s, are examples of parallel trajectories in the two nations considered.